Pitfalls of pay transparency: Evidence from the lab and the field - Katharina Brütt; Huaiping Yuan (Tinbergen Institute, 2022)
Wage transparency regulation is widely considered and adopted as a tool to reduce the gender wage gap. We combine field and laboratory evidence to address how and when wage transparency can be effective and explore the role of belief adjustments as a mechanism. In the field, this paper studies a German wage transparency policy that allows employees to request wage information of comparable employees. Exploiting variation across firm size and time, we first provide causal evidence that this regulation does not affect the gender wage gap. In an online laboratory experiment, we study whether the failure of this policy hinges on two aspects: (1) the endogenous availability of wage information, and (2) the absence of performance information. Our data underline the importance of both factors. In contrast to endogenously acquired wage information, exogenously provided wage information does increase overall wages. So does the provision of performance information. However, none of these types of information reduce the gender wage gap. Wage information even deters women from entering negotiations.
Keywords: J08; J16; J31; C91; 330; Gender pay gap; Negotiations; Transparency